Accurate Efficiency Measurements of Organic Light‐Emitting Diodes via Angle‐Resolved Spectroscopy. Issue 1 (8th November 2020) - Archer, Emily; Hillebrandt, Sabina; Keum, Changmin; Murawski, Caroline; Murawski, Jan; Tenopala‐Carmona, Francisco; Gather, Malte C.
Abstract: The accurate characterization of thin‐film light emitting diodes (LEDs)—including organic light emitting diodes (OLEDs), perovskite LEDs, and quantum dot LEDs—is crucial to the understanding of the factors that influence their efficiency and thus to the fabrication of LEDs with improved performance and stability. In addition, detailed information about the angular characteristics of LED emission is useful to assess the suitability of individual architectures, e.g., for display applications. Here, the implementation of a goniometer‐based measurement system and corresponding protocol are described that allow to accurately determine the current–voltage–luminance characteristics, external quantum efficiency, and luminous efficacy of OLEDs and other emerging thin‐film LEDs. The system allows recording of angle‐resolved electroluminescence spectra and accurate efficiency measurements for devices with both Lambertian and non‐Lambertian emission characteristics. A detailed description of the setup and a protocol for assembling and aligning the required hardware are provided. Drawings of all custom parts and the open‐source Python software required to perform the measurement and to analyze the data are included. Abstract : Accurate characterization of organic light‐emitting diodes (OLEDs) is crucial for optimizing their efficiency, performance, and stability. Here, the implementation of a goniometer‐based measurement system and the analysis protocol are described that accurately determine the current–voltage–luminance characteristics, external quantum efficiency, and luminous efficacy of OLEDs regardless of whether they show Lambertian emission.